Dynamic Linkages among Stocks and Commodities: A Switching Copula Approach - Hina Munir Abbasi; Naveed Raza (Journal of Management Practices, Humanities and Social Sciences, 2022)
The fluctuating behavior of financial markets has significant impact on economic variables. A relatively new modeling technique, “switching dependence copula” is employed to characterize conditional dependence among stock indices (Islamic/conventional stocks) and commodities. As the dependence may switch in between negative and positive correlation regimes with the passage of time where the copula captures dependence structure more conveniently and portrays pictures most relevantly then a single copula regime. The sample period ranges from 2011 to 2021. All the data sourced from Thomson Reuters. Overall, the results are in favor of commodities phenomenon of providing better hedging and diversification benefit to stock indices. Fluctuating behavior is observed for Islamic stocks and commodities pairs. According to the results, commodities are suitable as cousin during crisis period, especially during negative correlation regime; commodities perform better, providing hedging and diversification benefits.